Pelatihan Entrepreneurship Berbasis Keterampilan Menulis Cerpen dengan Metode “Showing Not Telling” bagi Siswa MAN Insan Cendikia Jambi: Entrepreneurship Training Based on Short Story Writing Skills Using ‘the Showing Not Telling” Method for MAN Insan Cendikia Jambi - Hidayati, Hidayati; Sartika, Delita; Al Arif, Tubagus Zam Zam; Armiwati, Armiwati; Kurniawan, Dedy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Several writing achievements have been achieved by students of Madrasah Aliyah Negeri (MAN) Insan Cendikia Provinsi Jambi, namely 1st place in the 2018 National level Poetry Writing Competetion, 2020 National Level Essay Competition, Critical Essay Writing Finalist, 3rd place in the 2021 Balitbangda Scientific Writing Competition. Seeing their potential, the community service team held creative writing training and one of them is short story writing. This community service program aims to improve students’ ability to write short stories. This community service activity which was attended by 120 students were carried out through training and mentoring for students using the “Showing Not Telling” method. The outputs of this community service are students’ short stories of MAN Insan Cendikia Provinsi Jambi uploaded in the Padlet.